PERSEPSI GURU DAN SISWA TENTANG LOKASI RAWAN BANJIR DI SMAN 5 SUNGAI PENUH - Dwi Frila Dinasti; Afdhal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to (1) determine teachers' perceptions of flood-prone locations at SMAN 5 Sungai Penuh and (2) determine students' perceptions of flood-prone locations at SMAN 5 Sungai Penuh. A descriptive qualitative approach was used with data collection through in-depth interviews, observation, and documentation. Informants consisted of the principal, vice principal, teachers, and students in grades X, XI, and XII. Data analysis followed the interactive model of Miles and Huberman: data reduction, data presentation, and drawing conclusions and verification. The results show that teachers perceive flooding as a serious risk that disrupts the continuity of learning through damaged facilities, access barriers, and reduced effective learning time. Mitigation efforts have been made, including building elevation and online learning, but their implementation has not been optimal due to limited infrastructure and internet networks. The impact of flooding also extends to students' psychological aspects, in the form of decreased motivation and concentration. From students' perceptions, flooding is perceived as a major obstacle because it disrupts mobility, reduces learning comfort, and reduces the effectiveness of learning time at school and at home. Overall, flooding impacts both the physical aspects of education (facilities and access) and the non-physical aspects (psychological aspects and the learning process). Teachers' and students' perceptions are shaped by repeated experiences with flooding, reinforcing risk awareness and necessitating more comprehensive mitigation strategies to ensure the sustainability of education in flood-prone areas.